The Skinny on Low-fat and Fat-free Milk and Milk Products - Lauren Headrick; Karla P. Shelnutt (EDIS, 2011)
Whether you are young or old, consuming fat-free and low-fat milk products every day is important for good health. This 5-page fact sheet highlights the purpose of including foods from the Milk group in the diet and the daily amounts needed for children and adults. It also includes helpful hints for those who are lactose intolerant. Lastly, there are tips for how to increase your daily intake of milk and milk products. Written by Lauren Headrick and Karla P. Shelnutt and published by the UF Department of Family Youth and Community Sciences, April 2011.